G23 What is the impact on nursing staff caring for children where legal judgements have been sought to withdraw life-sustaining therapy?. (12th March 2018) - Schofield, C; Playfor, S
Abstract : Aims: In recent years legal judgements have being sought more frequently seeking withdrawal of life-sustaining therapy (LST) for patients in paediatric intensive care units (PICUs). However, there is limited information regarding the impact these cases have on nursing staff. This research aims to explore the impact on staff caring for children where legal judgements have been sought to withdraw LST. Methods: Qualitative research was conducted using data collected from semi-structured interviews. A purposive sample was selected ensuring all participants have had experience caring for children in these circumstances. Exploratory research enabled detailed insight into the impact of these situations in addition to participant's experiences and perspectives. Results: Our findings have shown that the majority of participants feel caring for these children impacts negatively on their mood; this was commonly associated with beliefs that the nursing role actively contributes to prolongation of suffering. Managing relationships with the child's family has been found to be one of the most demanding aspects of caring for children when such judgements are sought. A number of complex components involved in the formation and maintenance of these relationships have been explored, all of which appear to result in significant additional stresses for the nursing staff involved. Further findings suggest that less experienced staff find it harder to dissociate themselves from the emotional aspects of these situations and as a result experience more psychological impact. Despite this, relatively little senior support is routinely offered; participants felt that this is due to the relative clinical stability of the children. Consequently, staff morale is perceived to be low when such children are on the unit. Conclusion: Our findings highlight numerous contributors that are involved in nursing staff being negatively impacted by caring for children where legal judgements have been sought to withdraw LST.